PENGARUH CO-BRANDING DAN TARIF TERHADAP KEPUTUSAN MENGGUNAKAN OPERATOR CDMA FREN :Survei pada Pengguna Fren di Gallery Fren BEC Kota Bandung - , Ricke Annissa Dellyasary, - (2008)
The potential growht of mobile phone costumers which shows increasing trend that draws attention to investors to invest in service field. It causes the growth of telecommunication indusrty in Indonesia and makes the competition in telecommunication service field. On 2002, there was telecommunication technology used CDMA which has many superiority. The development of CDMA telecommunication technology makes other CDMA telecommunication operator appeared such as Telkom as pioneer, Fren, Esia and StarOne. Market segmen of CDMA in Bandung is dominated by Esia 49,72%, Telkom Flexi 34,11%, Then Fren 15,55% and the last is StarOne 0,63%. The decision to buy that have by fren costumers in bandung can be seen from the market segment that only 15,55% mobile phone user are from customers. That number producer create any marketing programs that can make the competition composure. That case is the reason to do this research, which is about the influence of co-branding and cost to the decision to use fren CDMA telecommunication operator. The object of this research is fren costumers in fren gallery in BEC Bandung. Free variabel in this research is co-branding (X1) and cost (X2) while the bound is decision to use (Y). The type of this reseach is descriptive verifikatif with explanatory survey method. The numbers of samples in this reseach are 100, which get by simple ramdom sampling technique. Data analysis and hypothesis test use (phat analysis) that supperted by software SPSS 15, this phat analysis technique is used to know the direct or indirect